UV light induced accumulation of variability in a diploid strain of Aspergillus nidulans - A Marini; S PIMPINELLI; N MATMATI; N BABUDRI; G MORPURGO (Fungal Genetics Reports, 1998)
The accumulated variability in asexual species was evaluated in Aspergillus nidulans diploid cells after repeated cycles of UV irradiation. The results show that diploid cells can accumulate a very high genetic variability in the heterozygous condition as previously shown with the base analog 6-N-hydroxylaminopurine (HAP).